Recent Referees (Journal of Political Economy, 2019)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:George AkerlofDavid AlbouyJames AlbrechtHunt AllcottFranklin AllenDouglas AlmondAnnette AlstadsaeterMichael L. AndersonPeter ArcidiaconoLutz ArnoldRichard ArnottJeremy AtackEnghin AtalayEduardo AzevedoNick BloomChristopher BollingerStephane BonhommeJaroslav BorovickaJohn BoundYann BramoulleWilliam BrockBen BrooksLeonardo BursztynDavid ByrnePedro CarneiroFrancesco CaselliDavin ChorSteve CicalaGregory ClarkTommaso ColussiGiovanni CompianiJ. Anthony CooksonJames DanaDavid de MezaWouter DesseinPaul DevereuxJonathan DingelWioletta DziudaLena EdlundRuben EnikolopovJoan EstebanFernanda EstevanConstanca Esteves-SorensonRobert FeenstraGeoffrey FisherRaymond FismanJon H. FivaChristopher FlinnTeresa FortMarco FrancesconiSharat GanapatiJorge GarciaJodi GardnerDaniel GarrettMaitreesh GhatakClaudia GoldinMichael GraberDavid GreenFaruk GulNaijia GuoPeter HaanMarina HalacJonathan HallNathaniel HendrenDavid HirshleiferGerard HobergRichard HoldenKerstin HolzheuPeter HullRobert HuntIl-Myoung HwangAri HyytinenKoichiro ItoLakshmi IyerJustin JohnsonBenjamin JonesCharles JonesShawn KantorLouis KaplowMaximilian KasyMichael KatzRyan KelloggJun Hyung KimPatrick KlineScott KominersFrancis KramarzClaus KreinerPer KrusellLorenz KuengDavid LagakosRasmus LandersoeKurt LavettiRamanan LaxminarayanLars LefgrenRasmus LentzFei LiMatthew LindquistElliot LipnowskiCorinne LowJingfeng LuFernando LucoErzo LuttmerThierry MagnacJames MalcomsonNiko MatouschekMargaret McConnellJohn McLarenHalvor MehlumNathan MillerRobert MillerBenny MoldovanuNick NetzerCarlos NotonNathan NunnWojciech OlszewskiErwin OogheHessel OosterbeekPhilip OreopoulosAmanda PallaisRaphael ParchetJohn PepperFranco PeracchiNicola PersicoPer Pettersson-LidbomFlorenz PlassmannMaria PolyakovaHillel RapoportStephen RaudenbushDoron RavidCollin RaymondStephen ReddingPhilip RenyJean-Marc RobinJorge RodriguezJean-Laurent RosenthalMark RosenzweigMarzena RostekNicholas RyanBruce SacerdoteDaniel SacksNicolas SahuguetRaul Sanchez de la SierraCarlos SanzSimone SchanerJose ScheinkmanLinda SchillingKarl SchurterPetr SedlacekJoseph ShapiroJonathan ShawAndrew ShephardRobert ShimerTimothy SimcoeAndrey SimonovEric SimsAlp SimsekJoel SlemrodJeff SmithLones SmithJenna StearnsKjetil StoreslettenBruno StruloviciJohn SuttonJeroen SwinkelsGuido TabelliniPetra ToddRagnar TorvikSarah TurnerGabriel UlysseaDimitri VayanosPedro VicenteEdward VytlacilSarit WeisburdIvo WelchEric WeylMatthijs WildenbeestHeidi WilliamsMatthew WiswallAlexander WolitzkyWei XiongDeniz YavuzAli YurukogluAnastasia ZakolyukinaHanzhe ZhangJin Zhou Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 2April 2019 Article DOIhttps://doi.org/10.1086/703848 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.